Teknik Equivalence Partitions untuk Pengujian Aplikasi Manajemen Kas dan Inventaris Berbasis Web - Dwi Ismiyana Putri (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Performing checks on software specifications requires testing and validation. The discrepancy in the data entry process was caused by the validation process not being optimized. One of the consequences is the process of failure when inputting data. As a result, the application can be dangerous for future system users. Therefore, it is necessary to improve the quality and accurate verification. When the testing process finds errors that were previously unknown, then the test is called a good test. One of the testing method is the black box testing method with the Equivalence Partition technique. Equivalence Partition is a technique used to reduce the number of test cases that exist during testing, by entering data on each form that is in the application in each menu, then testing and grouping based on the validity by the system functionality.